2016
DOI: 10.1098/rstb.2015.0399
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to provocative questions in left–right asymmetry

Abstract: Left–right asymmetry is a phenomenon that has a broad appeal—to anatomists, developmental biologists and evolutionary biologists—because it is a morphological feature of organisms that spans scales of size and levels of organization, from unicellular protists, to vertebrate organs, to social behaviour. Here, we highlight a number of important aspects of asymmetry that encompass several areas of biology—cell-level, physiological, genetic, anatomical and evolutionary components—and that are based on research con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Crayfish use their limbs during aggression; asymmetries of limb performance could affect this behavior (Angilletta and Wilson 2012). Levin et al (2016) have suggested that left and right asymmetries in organisms arise from embryogenesis. 6 th AG develops from two embryonic neuromeres in the crayfish Procambarus clarkii (Kondoh and Hisada 1986;Mulloney et al 2003), and the CPR-axons are in the ventral cord, in Wiersma area 82 for the left hemicord, and in area 79 of the right hemicord of the cord map of the crayfish (Hermann 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Crayfish use their limbs during aggression; asymmetries of limb performance could affect this behavior (Angilletta and Wilson 2012). Levin et al (2016) have suggested that left and right asymmetries in organisms arise from embryogenesis. 6 th AG develops from two embryonic neuromeres in the crayfish Procambarus clarkii (Kondoh and Hisada 1986;Mulloney et al 2003), and the CPR-axons are in the ventral cord, in Wiersma area 82 for the left hemicord, and in area 79 of the right hemicord of the cord map of the crayfish (Hermann 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Left–right asymmetry is a fundamental property that is widely observed across species, such as in the position of visceral organs and lateralized brain functions 1 , 2 . Despite a significant influence of left–right asymmetry on the body plan, its precise phenomenon, underlying molecular mechanisms and functional roles in the organisms still remain unclear 3 . With regard to the initial symmetry-breaking step, it was postulated that the molecular handedness or chirality is converted to a cellular and multicellular asymmetry that finally leads to left–right asymmetry in the organisms 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Left-right asymmetry is a characteristic of the brain from vertebrate species and some invertebrate species [24], which arises from embryogenesis in the organism [25][26][27]. Crustacean decapods showed the left and right asymmetry in some anatomical regions [28][29][30].…”
Section: Introductionmentioning
confidence: 99%